STUDY ON THE IMPLICATIONS OF THE APPLICATION OF THE SPECIFIC TAX ON THE PROFITABILITY OF ECONOMIC ENTITIES IN TOURISM AND PUBLIC FOOD - Alina MARCUTA; Liviu MARCUTA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In this article we aim to present how the application of the specific tax in tourism and food influences the profitability of economic entities in this field. The research methodology involved the study of the literature, the accounting regulations regarding the specific tax and the analysis performed for a number of 10 economic entities that apply these regulations. The study was based on quantitative and qualitative research that involved the collection of information provided by the financial statements, but also other information obtained based on a questionnaire applied to the entities in the study sample. The calculation methodology provided in Law 170/2016 on the establishment of the specific tax was also used. Following this research, we aimed to highlight both the way of applying the specific taxation within the entities in the field subject to analysis, but also the way in which this system influences the registered financial performance. At the same time, there were identified the advantages and disadvantages of its application. Based on the results obtained during the research, the conclusions were formulated regarding the efficiency of the application of the calculation system of the specific tax in the units with tourist and food profile.